Pengaruh Video Edukasi Obesitas Terhadap Pengetahuan dan Sikap Karyawan Tentang Obesitas (Pada SDM Non Nakes di RSUP Dr Sardjito Yogyakarta) - Ediana Kurniawati; Surahma Asti Mulasari; Sunarti Sunarti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of obesity education videos on knowledge and attitudes towards obesity and their effectiveness in non health workers at Dr. Sardjito Hospital Yogyakarta. The research method used was quasi experimental with pretest-posttest control group design. The intervention test was carried out by giving obesity education videos to the intervention group. The results showed that there was a significant increase in knowledge in the intervention group after giving obesity educational videos (p = 0.000), while in the control group there was no significant change (p = 0.083). However, in the aspect of attitude, both intervention and control groups did not show significant changes (p> 0.05). This shows that educational videos are effective in increasing knowledge, but do not significantly affect changes in attitudes towards obesity. The conclusion of this study is that educational videos can be used as an effective medium in delivering health information to improve knowledge, but to achieve attitude improvement, comprehensive methods are needed, including social interaction and direct experience